(untitled) - Trần, Lê Cẩm Tú (Netherlands, 2019)
This study investigated the nutritional interventions to alter/improve faecal pellet quality (which could lead to better and more complete removal of faecal waste) and the enhancement of the stability of egested faeces. In this thesis, striped catfish was taken as a model species, to study the options for aquaculture waste management. Up till now, it is not clear if nutritional interventions targeted to reduce the amount of faecal waste can go along with improving the faecal quality. The main aim of this research was to study the impact of different nutrition interventions on both the quantity and quality of faecal waste produced by striped catfish (Pangasianodon hypophthalmus, Sauvage, 1878).
Phương pháp nghiên cứu kinh tế - Xã hội nghề cá
Keywords: Cá nước ngọt,Freshwater fishes